Influence of Product Quality, Promotion, and Price on the Purchase Decision of Glad2Glow Products among Students in Semarang - Sifa’ul Nur Azizah; Khasan Setiaji (Universitas KH. Abdul Chalim Mojokerto, 2025)
The cosmetics industry in Indonesia has experienced rapid growth in line with increasing consumer interest in skincare products. One of the emerging local brands is Glad2Glow, which has successfully gained attention through social media, particularly TikTok. However, intense competition with other brands and consumer trust issues related to product claims have created dynamics in purchasing decisions. This study aims to analyze the influence of product quality, promotion, and price on the purchasing decisions of Glad2Glow products among students in Semarang City. The research employed a quantitative approach with a causal design. The sample consisted of 385 respondents selected using purposive sampling, with criteria including students aged 13–18 years, residing in Semarang, and having used Glad2Glow products at least twice. The research instrument was a questionnaire based on a four-point Likert scale, and the data were analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression with SPSS version 21. The findings reveal that product quality, promotion, and price have a positive and significant effect on purchasing decisions. Partially, product quality shows a regression coefficient of 0.276, promotion 0.234, and price 0.342. Simultaneously, these three variables contribute 79.9% to purchasing decisions, while the remaining 20.1% is influenced by other factors not examined in this study. These results emphasize that improving product quality, implementing effective promotional strategies, and setting appropriate prices can encourage consumers, particularly students, to purchase Glad2Glow products.